HUBUNGAN STATUS PERKAWINAN APOE 4 DAN JENIS AKTIVITAS FISIK TERHADAP PENURUNAN KOGNITIF PADA LANSIA PEREMPUAN - Nicholas Andrian Singgih,* Yuda Turana,* Yvonne Suzy Handajani,* Nelly Tina Widjaja,* Linda Suryakus (NEURONA, 2019)
INTRODUCTION THE NUMBER OF ELDERLY POPULATION IN INDONESIA CONTINUES TO INCREASE EVERY YEAR ESPECIALLY WOMEN ELDERLY WOMEN ARE AT HIGHER RISK OF EXPERIENCING DECREASED COGNITIVE FUNCTION